2022
DOI: 10.1002/ps.6816
|View full text |Cite
|
Sign up to set email alerts
|

Chlorothalonil alters the gut microbiota and reduces the survival of immature honey bees reared in vitro

Abstract: BACKGROUND Chlorothalonil is a nonsystemic fungicide, and it is one of the most widely detected pesticides in bee hives. The effect of chlorothalonil on the survival, weight, and gut microbiota of immature Apis mellifera L. reared in vitro was studied. RESULTS Larvae were fed 1, 2, 4, 8, and 16 μg/mL chlorothalonil and compared with larvae fed the negative control (diet without any additives), positive control (45 mg/L dimethoate), and solvent control (2% acetone). Compared with the control groups, the surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Chlorothalonil reacts with multiple thiol-dependent proteins, thus eventually building up toxicity in bacterial cells ( 26 , 31 ). In fact, chlorothalonil impacts on bacteria have been widely documented in soil, rhizosphere, pollinators, and amphibian skin ( 33 35 , 53 55 ). In this study, the abundance of Pantoea , Brevundimonas , and Lichenihabitans was consistently elevated by Daconil and Concert II, indicating that Gram-negative bacteria may have some tolerance to chlorothalonil ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorothalonil reacts with multiple thiol-dependent proteins, thus eventually building up toxicity in bacterial cells ( 26 , 31 ). In fact, chlorothalonil impacts on bacteria have been widely documented in soil, rhizosphere, pollinators, and amphibian skin ( 33 35 , 53 55 ). In this study, the abundance of Pantoea , Brevundimonas , and Lichenihabitans was consistently elevated by Daconil and Concert II, indicating that Gram-negative bacteria may have some tolerance to chlorothalonil ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, propiconazole may not act directly on bacteria, as they lack sterols in their cell structure, and the observed effects of propiconazole on bacterial communities are instead considered to be associated with microbial competition ( 30 ). Chlorothalonil, on the other hand, can bind to glutathione and deactivate thiol-dependent enzymes in bacteria ( 31 ) and thus has shown a direct impact on various bacterial communities in soils ( 32 , 33 ), pollinator guts ( 34 ), and aquatic systems ( 35 ). In particular, Chen et al ( 36 ) showed that soil bacteria involved in nitrogen cycling were affected by chlorothalonil applied at the label rate in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The disappearance of honey bees is only the most visible part of a widespread phenomenon due to massive loss of biodiversity that negatively impacts agroecosystems [62]. The fungicide Chlorothalonil has been shown to alter the intestinal bacterial communities of honey bees, in addition to decreasing larval survival in the hive [63]. However, growers continue to rely on the chemical, without considering the negative effects for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org fungicides and neonicotinoids are commonly used in agriculture and have been found in bee bread, beeswax and foraged environment (McAfee et al, 2021). Although not acutely toxic to bees, several studies have reported potential sublethal effects of chlorothalonil and acetamiprid, particularly in larvae (Wagner et al, 2021;Wu et al, 2022). In this study, we investigated the chronic toxicity of chlorothalonil and acetamiprid on developing larvae.…”
Section: Figurementioning
confidence: 99%
“…As a fungicide, chlorothalonil may affect the fungal community in the honey bee gut. Our previous work showed that chlorothalonil significantly decreased the survival rate of immature bees and altered the gut microbiota of newly emerged honeybees when exposure concentrations were higher than 2 μg/mL ( Wu et al, 2022 ). Acetamiprid is a representative of the first generation of neonicotinoids with broad-spectrum characteristic, widely used to control destructive agricultural pests ( Shi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%